Pedagogy in learning society - Pljakić, Goran D (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The author starts from the thesis that in the future a man will have to become more flexible and changeable than he has ever been, due to dynamic social changes. The nature of these circumstances is determined by the society of the 21st century being  a "learning society". In fact, in order for each individual to be able to cope with the rapid changes he/she faces, hes/she must be able to use knowledge (information) as one of the main economic resources of today to strategically plan changes in education. This paper also discusses the issues of the place and potential directions in which the pedagogy will have to develop and change within the learning society.
Keywords: learning society; social change; strategic planning; knowledge; pedagogy